Trends in the formation of state regional demographic policy in Ukraine - Yavorska, V.; Gorodetskaya, D.; Yurash, Ya. (Journal of Education, Health and Sport, 2020)
The problems of formation of regional policy and stages of formation and growth of geodemography as modern scientific field of population geography were reviewed in details in the article. In the first stage, a central place in the system of knowledge of the population belongs to the demographics. The second stage are increased by interaction of demography with other sciences, including geography. At their junction, a new discipline - population geography. In the third stage are forming the new direction of population geography - geodemography which orientated to the study of regional differences of population and resettlement and development of a regional demographic policy.